Keeping doctor-patient confidentiality - Wroński, Konrad (Contemporary Oncology/Współczesna Onkologia, 2007)
Every medical doctor must keep doctor-patient confidentiality. It is unacceptable to inform the patient family personaly and especially over the telephone unless patient has previously expressed his or her concern. Even the patient death does not exempt the doctor from the keeping doctor-patient confidentiality. The following article presents legal aspects related to keeping doctor-patient confidentiality.